People Analytics: far beyond the data - Moraes, Silvana de Souza [UNESP] (2021)
Introduction: this study aims to develop a review about People Analytics based on the literature in the area available in theWeb of Science and Scopus databases. The concept was explored, as well as studies that demonstrate how to use it in organizations, the advantages and challenges of its application and the perception of managers about this application. Method: the research was carried out based on articles available in the above-mentioned databases, published from 2005 onwards. Results: the results show that special attention should be given to the origin of the analyzed data, as well as a correct analysis of the available material is fundamental in order to generate information and knowledge that represent value for the organizations. Conclusions: it is also important to note that the training of Human Resources professionals in the use of data is emphasized in several articles that composed the analysis reported in this study.